NK Cells in Ascites From Liver Disease Patients Display a Particular Phenotype and Take Part in Antibacterial Immune Response - Lutz, Philipp; Jeffery, Hannah C.; Jones, Nicholas; Birtwistle, Jane; Kramer, Benjamin; Nattermann, Jacob; Spengler, Ulrich; Strassburg, Christian P.; Adams, David H.; Oo, Ye H. (Frontiers in Immunology, 2019)
Background and Aims: Ascites and spontaneous bacterial peritonitis are frequent complications of liver cirrhosis. In spite of the clinical impact, little is known about ascites as an immune cell compartment. Therefore, we analyzed NK cells in blood, ascites and liver. Methods: Mononuclear cells from blood, ascites and liver explants of patients with advanced liver disease were extracted by density gradient centrifugation. Phenotyping and analysis of functional responses were carried out using flow cytometry. Migratory potential was investigated with transwell chamber assays. NK cell metabolism was assessed by Seahorse technology. Results: NK cell frequency was increased in uninfected ascites compared to blood, but not to liver. Ascites NK cells were predominantly CD16positive. CD56bright ascites NK cells did not share the typical phenotype of their liver counterparts. In contrast to the inhibitory receptor NKG2A, expression of the activating receptor NKG2D was decreased on ascites and liver CD16positive NK cells. Ascites NK cells expressed higher levels of CXCR3 than blood or liver NK cells, corresponding to increased ascites levels of CXCL10. Blood NK cells migrated towards ascites. Stimulation of mononuclear cells with Escherichia coli led to downregulation of NKG2D expression and IL-12 and IL-18 mediated secretion of interferon-γ by ascites and liver, but not blood NK cells. In-vivo, ascites NK cells expressed higher levels of the activation marker CD69 and lower levels of NKG2D during spontaneous bacterial peritonitis compared to uninfected ascites. Conclusion: Ascites NK cells display a particular phenotype and are implicated in local immune defense against translocating bacteria.